Trends of rainfall in Sarawak & its impact on tourism / Rafidah Husen ... [et al.] - Husen, Rafidah; Tuh, Moi Hua; Robin, Chang Yee Hui (2011)
An ablotlc factor such as weather can be disruptive to certain businesses Weather sensitive businesses (WSB) such as agriculture, construction, retail, transportation and tourism (travel and leisure) are often the first to feel the financial Impact of severe or changing weather Many WSB do not regularly quantify weather Impact on performance, and such few have developed comprehensive strategies for managing weather risk The impact of extreme weather on WSB occurs all over the world including Sarawak. However, there are limited studies on weather impacts on businesses especially at a local level Therefore it IS significant and necessary to conduct this study as a preliminary step to help businesses better understand local rainfall patterns/trends and volatility trends to ensure good planning and rtsk mitigation for the future